Hybrid Treatment with Complete Transposition of Supra-Aortic Trunks versus Conventional Surgery for the Treatment of Aortic Arch Aneurysm - Souza,Leonardo de Oliveira (2017)
Abstract Objective: The disease of the aortic arch is traditionally approached by open surgical repair requiring cardiopulmonary bypass and circulatory arrest. This study performed a retrospective analysis comparing outcomes through primary hybrid patients submitted to aortic arch surgery without cardiopulmonary bypass with patients submitted to conventional open surgery. Methods: 25 patients submitted to the aortic arch surgery were selected in the period 2003-2012 at the Madre Teresa Hospital in the city of Belo Horizonte, Brazil; 13 of these underwent hybrid technique without cardiopulmonary bypass and 12 underwent conventional open surgery. Results: The mortality rate for the hybrid group was 23% and for the conventional surgery group was 17% (P=0.248). The postoperative complication rate was also similar in both groups, with no significant difference. Conclusion: Both techniques proved to be similar in mortality and morbidity. However, due to the small sample, more analytical studies with larger samples and long-term follow-up are needed to clarify this issue.